IL-22 Plays a Critical Role in Maintaining Epithelial Integrity During Pulmonary Infection - Alcorn, John F. (Frontiers in Immunology, 2020)
Pulmonary infection is a leading cause of hospitalization in world. Lung damage due to infection and host mediated pathology can have life threatening consequences. Factors that limit lung injury and/or promote epithelial barrier function and repair are highly desirable as immunomodulatory therapeutics. Over the last decade, interleukin - 22 has been shown to have pulmonary epithelial protective functions at the mucosal immune interface with bacterial and viral pathogens. This article summarizes recent findings in this area and provides perspective regarding the role of IL-22 in mucosal host defense.